Evaluation of the Effects of Different Bacteroides vulgatus Strains against DSS-Induced Colitis - Sijia Li; Chen Wang; Chengcheng Zhang; Yanhong Luo; Qianqian Cheng; Leilei Yu; Zhen Sun (Journal of Immunology Research)
Although the strain-dependent effects of Bacteroides vulgatus on alleviating intestinal inflammatory diseases have been demonstrated, the literature has rarely focused on the underlying causes of this effect. In this study, we selected four B. vulgatus strains (FTJS5K1, FTJS7K1, FSDTA11B14, and FSDLZ51K1) with different genomic characteristics and evaluated their protective roles against dextran sulfate sodium- (DSS-) induced colitis. Compared to the other three tested strains, B. vulgatus 7K1 more strongly ameliorated the DSS-induced weight loss, shortening of the colon length, increased disease activity index scores, colonic tissue injury, and immunomodulatory disorder. In contrast, B. vulgatus 51K1 significantly worsened the DSS-induced alterations in the tumor necrosis factor-alpha (TNF-α) concentration and colonic histopathology. A comparative genomic analysis of B. vulgatus 7K1 and 51K1 showed that the beneficial effects of B. vulgatus 7K1 may be associated with some of its specific genes involved in the production of short-chain fatty acids or capsular polysaccharides and enhancement of its survivability in the gut. In conclusion, these findings indicate that the supplementation of B. vulgatus 7K1 is a potentially efficacious intervention for alleviating colitis and provides scientific support for the screening of probiotics with anticolitis effect.